Pathways of Metropolitan cities and Urban requirements of tomorrow (Damascus University Journal for engineering sciences, 2021)
The metropoles and metropolitan concept represent a spatial demand for cities, as it reflects their development, regulates their dynamics and introduces them in the context of globalization. The spatial tripartite applied especially to the world capitals (City, Agglomeration-Metropole), is a methodological and reference paper that can be used for economic, social, environmental and administrative development. In this context, the problem of Damascus City appears in the difficulty of understanding its spatial relations and the lack of the adoption of appropriate urban conceptions, and thus the challenge of entering the competitiveness and funding in the reconstruction and subsequent stages of development. The research aims to analyze and evaluate the Metropole phenomena and to show the methodological pathways that influence the urban development within the context of Metropole, to determine the planning considerations and the spatial requirements of the metropolitan cities and to explore the new urban context of Greater Damascus.
Keywords: Metropolitan; Damascus Metropole; Peri-urbanization; Agglomeration; Aire Urbaine; Globalization